Class Size and Academic Performance of Primary School Pupils in English and Mathematics in Rivers State - Ibiye Omieibi-Davids (Researchparks Publishing, 2022)
The study used the ex-post-facto research design to examine the appropriateness and effect of age on academic performance of primary school children in Rivers State in English Language and Mathematics. Simple random and stratified sampling techniques were used to choose 498 Primary 4 pupils from 29 classes of 20 schools in 5 local government areas of Rivers state and their teachers. The instruments of the study were English and Mathematics Competency Test (EMCT) which was used to collect information about the academic performance; the Class size and Primary School Pupils Performance Questionnaire (EPSPPQ) was used to collect information on the number of children in the class. The study had 2 research questions and 1 hypothesis. The research questions were answered with mean and standard deviation, while the hypothesis was tested with t-test at a significance level of 0.05. The result showed that class size was appropriate in majority of the schools. Only 24.3% of the classes used in the study had more than the recommended 35 pupils. The size of the class had no significant impact on the academic performance of the learners. The researcher believed that the class sizes might have been affected by the Covid-19 restrictions of 2020 and recommend further studies to be done in this area with a much bigger sample.